Design of channel filter based on asymmetric one-dimensional defective photonic crystal for broadband responses - Asmar Aming (2018)
A study of the asymmetric geometry based on a one-dimensional defective photonic crystal is reported. A common structure in the form of (HL)4L(HL)4 is numerically investigated to be suitable for channel filters with broadband responses. The transmission characteristics, analysed by the Transfer Matrix Method (TMM), of the proposed structure in UV, VIS and IR ranges are clearly illustrated. A number of interesting features on the defect modes such as transmittance level, filtering frequency and the number of modes are observed when the defect layer thickness is adjusted. The results show a promising potential of the designed channel filter for various applications including the optical communication.